THE SUSCEPTIBILITY OF RECENT ISOLATES OF Schistosoma mansoni TO PRAZIQUANTEL - Adriana Maria B. MENDONÇA; Ana Paula S. FEITOSA; Dyana L. VERAS; Thiago J. MATOS-ROCHA; Marília G. dos Santos CAVALCANTI; Constança Clara G. S. BARBOSA; Fábio A. BRAYNER; Luiz C. ALVES (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
Introduction: Schistosomiasis is a chronic disease caused by trematode flatworms of the genus Schistosoma and its control is dependent on a single drug, praziquantel (PZQ), but concerns over PZQ resistance have renewed interest in evaluating the in vitro susceptibility of recent isolates of Schistosoma mansoni to PZQ in comparison with well-established strains in the laboratory. Material and methods: The in vitro activity of PZQ (6.5-0.003 µg/mL) was evaluated in terms of mortality, reduced motor activity and ultrastructural alterations against S. mansoni. Results: After 3 h of incubation, PZQ, at 6.5 µg/mL, caused 100% mortality of all adult worms in the three types of recent isolates, while PZQ was inactive at concentrations of 0.08-0.003 µg/mL after 3 h of incubation. The results show that the SLM and Sotave isolates basically presented the same pattern of susceptibility, differing only in the concentration of 6.5 µg/mL, where deaths occurred from the range of 1.5 h in Sotave and just in the 3 h range of SLM. Additionally, this article presents ultrastructural evidence of rapid severe PZQ-induced surface membrane damage in S. mansoni after treatment with the drug, such as disintegration, sloughing, and erosion of the surface. Conclusion: According to these results, PZQ is very effective to induce tegument destruction of recent isolates of S. mansoni.